The effects of stress and glucocorticoids on vocalizations: a test in North American red squirrels. (10th April 2019) - Sehrsweeney, Matt; Wilson, David R; Bain, Maggie; Boutin, Stan; Lane, Jeffrey E; McAdam, Andrew G; Dantzer, Ben
Abstract : If you are a stressed squirrel, your neighbors might be hearing about it. We found evidence that squirrels experiencing short-term stress produce vocalizations that are structurally distinct from unstressed squirrels. However, the mechanism is not so simple—the hormones released in response to stress (glucocorticoids) alone are not responsible for these acoustic changes. Abstract: Acoustic signaling is an important means by which animals communicate both stable and labile characteristics. Although it is widely appreciated that vocalizations can convey information on labile state, such as fear and aggression, fewer studies have experimentally examined the acoustic expression of stress state. The transmission of such public information about physiological state could have broad implications, potentially influencing the behavior and life-history traits of neighbors. North American red squirrels ( Tamiasciurus hudsonicus ) produce vocalizations known as rattles that advertise territorial ownership. We examined the influence of changes in physiological stress state on rattle acoustic structure through the application of a stressor (trapping and handling the squirrels) and by provisioning squirrels with exogenous glucocorticoids (GCs). We characterized the acoustic structure of rattles emitted by these squirrels by measuring rattle duration, mean frequency, and entropy. We found evidence that rattles do indeed exhibit a "stress signature." When squirrels were trapped and handled, they produced rattles that were longer in duration with a higher frequency and increased entropy. However, squirrels that were administered exogenous GCs had similar rattle duration, frequency, and entropy as squirrels that were fed control treatments and unfed squirrels. Our results indicate that short-term stress does affect the acoustic structure of vocalizations, but elevated circulating GC levels do not mediate such changes.